Low impact development technology : design methods and case studies - Clar, Michael L.; Traver, Robert G.; Clark, Shirley E.; Lucas, Shannon; Lichten, Keith; Ports, Michael A.; Poretsky, Aaron (American Society of Civil Engineers, 2015)
Selected papers from the 2011 Low Impact Development Conference, held in Philadelphia, Pennsylvania, September 25-28, 2011. Sponsored by the Low Impact Development Committee of the Urban Water Resources Research Council of the Environmental and Water Resources Institute of ASCE. As federal, state, and local governments realize that traditional approaches to stormwater management are not achieving the desired environmental protection goals, they are increasingly adopting low impact development (LID) technology as the preferred approach to stormwater management in land development and redevelopment. Low Impact Development Technology: Design Methods and Case Studies contains 22 papers that address a wide range of LID design applications and includes a number of practical case studies. Topics include: rain gardens and bioretention systems; green streets and hardscapes; green roofs; and watershed restoration. A companion volume, Low Impact Development Technology: Implementation and Economics, is also available.
Papers presented at the 2011 Low Impact Development Conference, held in Philadelphia, Pennsylvania, September 25-18, 2011.
Keywords: Urban runoff -- Management -- Congresses.; Sanitary engineering -- Congresses.; Sustainable development -- Congresses.; elektronické knihy; electronic books